Effect of viral infection on host protein synthesis and mRNA association with the cytoplasmic cytoskeletal structure (The Rockefeller University Press, 1985)
We studied the association of several eucaryotic viral and cellular mRNAs with cytoskeletal fractions derived from normal and virus- infected cells. We found that all mRNAs appear to associate with the cytoskeletal structure during protein synthesis, irrespective of their 5' and 3' terminal structures: e.g., poliovirus that lacks a 5' cap structure or reovirus and histone mRNAs that lack a 3' poly A tail associated with the cytoskeletal framework to the same extent as capped, polyadenylated actin mRNA. Cellular (actin) and viral (vesicular stomatitis virus and reovirus) mRNAs were released from the cytoskeletal framework and their translation was inhibited when cells were infected with poliovirus. In contrast, actin mRNA was not released from the cytoskeleton during vesicular stomatitis virus infection although actin synthesis was inhibited. In addition, several other conditions under which protein synthesis is inhibited did not result in the release of mRNAs from the cytoskeletal framework. We conclude that the association of mRNA with the cytoskeletal framework is required but is not sufficient for protein synthesis in eucaryotes. Furthermore, the shut-off of host protein synthesis during poliovirus infection and not vesicular stomatitis virus infection occurs by a unique mechanism that leads to the release of host mRNAs from the cytoskeleton.